Nasi Arab Arnab D’Qaseh / Nur Syuhada Muhammad … [et al.] - Muhammad, Nur Syuhada; Abas, Aemillyawaty; Hassian, Ummi Kalsum; Juri, Zuraini; Jonit, Azuanea; Othman, Zulaiha (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
The Malaysian Livestock Industries contributes 10.38 billion or 11.6% of 8.1% of Malaysia’s GDP in 2016 with the Poultry Industry’s 6.4% growth which contributes 95% of the total Livestock Industries GDP contribution. This shows the dependence of single supply of meat in Malaysia, therefore, there is an increasing need to diversify the protein source to the Malaysians. Recognizing this problem, the consumption of rabbit meat as an alternative source of food to substitute for chicken is very much recommended to the government to look for. Furthermore, among any other meats, rabbit meats are considered the healthiest because they contain the richest calcium and phosphorus and also the lowest cholesterol (Nistor, E., et al, 2013). Recommended by nutritionists over other meats, rabbit meat is valued for it is being lean, rich in proteins of high biological value, minerals, and vitamins. Besides, it has low concentrations of saturated fatty acids, cholesterol, and sodium (Gabriela et al., 2014). Therefore, introducing the new ready-to-eat product of Nasi Arab Arnab D’Qaseh would definitely encourage more people to consume rabbit meat in the most convenient way, healthy, and delicious. As Arabic Rice (Nasi Arab) has gained much popularity in Malaysia and is served with either lamb, mutton, beef or chicken, Nasi Arab Arnab D’Qaseh comes with special menú, which is not only the aromatic spice-infused baked rice oozes, but also the tender grilled rabbit meat with dipping sauce. Besides that, this pre-packed Nasi Arab is using retort processing technique to ensure the food product quality, especially in terms of its freshness, taste, aromas, its extended shelf life (can be consumed up to 2 years from the production date), the packaging is easy to be handled by customers and it ensures no deterioration in terms of the content quality by moisture, oxygen, ultraviolet, light, etc. within these two years of product consumption period. Therefore, with these benefits, Nasi Arab Arnab D’Qaseh would not only be the first to retort Nasi Arab with rabbit meat but also as a means to secure national food security.